Investment Arbitration: A Model for Resolving Property Law Disputes on the Example of Bosnia and Herzegovina and the Republic of Croatia? - Larisa Velić; Aida Mulalić; Enis Omerović (Društvene i Humanističke Studije, 2024)
Property disputes between Bosnia and Herzegovina and the Republic of Croatia are a reality that burdens the entirety of international diplomatic relations between two neighboring countries of the same subregion. After the dissolution of the Socialist Federal Republic of Yugoslavia (SFRY), numerous issues arose, of which property rights are among the most important. The republics of the former SFRY, as well as natural and legal persons, had their property in the entire territory of Yugoslavia, so it was necessary to adequately protect the existing rights. In this regard, in 2001, the Successor States of the SFRY concluded the Agreement on Succession, in which they agreed on movable and immovable property through seven Annexes. Bosnia and Herzegovina (BiH) started from the view that the comprehensive implementation of the Succession Agreement is the basis of permanent, stable, and friendly relations between the Contracting States and took all that was necessary to return the property claimed by the Successor States. However, the Republic of Croatia did not return the property in the way that Bosnia and Herzegovina did, and the first country started to violate the aforementioned multilateral international agreement. Given that the Agreement on Succession does not offer adequate solutions for the peaceful settlement of international disputes between the Contracting Parties, the paper analyzes the possibility of settlement of said disputes based on investment arbitration, which as a model for the settlement of international disputes is not an instrument used by individuals and legal entities from BiH into a sufficient extent. Equally, in this light, we explore the legal possibilities of the concluded Agreement on the Promotion and Protection of Investments between Bosnia and Herzegovina and the Republic of Croatia (bilateral investment treaty) and present the future of investment arbitration from the perspective of the European Union.